1986
DOI: 10.1161/01.str.17.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bruit, carotid and vertebrobasilar transient ischemic attacks--a clinical and ultrasonic correlation.

Abstract: SUMMARY One hundred patients with asymptomatic carotid bruit or transient ischemic attack (TIA) underwent continuous-wave Doppier (CWD) and real time ultrasound (RTU) testing of their cervical carotid arteries. After ultrasonic studies, 51 patients also underwent bilateral carotid angiography. There was 95 % agreement between CWD and angiography for the diagnosis of a significant (> 50 %) stenosis. The RTU diagnosis of a normal or occluded vessel was correct in 100% of cases. Seven plaques appreciated on RTU m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…One recent publication reported that plasma concentrations of total cholesterol were significantly higher in TLA patients with carotid stenosis than in controls. 22 Although in our study total cholesterol levels were not significantly related to carotid plaque, a significant relation might be found in a similar study with a larger sample size.…”
Section: -6 7-9 10-12 >12contrasting
confidence: 69%
See 1 more Smart Citation
“…One recent publication reported that plasma concentrations of total cholesterol were significantly higher in TLA patients with carotid stenosis than in controls. 22 Although in our study total cholesterol levels were not significantly related to carotid plaque, a significant relation might be found in a similar study with a larger sample size.…”
Section: -6 7-9 10-12 >12contrasting
confidence: 69%
“…In previous literature, there is little data to suggest that cigarette smoking is a risk factor for carotid disease; however, cigarette smoking has been found to be prevalent among patients with carotid disease. 22 In patients with transient ischemic attacks (TIAs), cigarette smoking was found to be significantly associated with a carotid disease score, 23 and in the Framingham Study, 24 smoking was found to be a risk factor for stroke, but only in men below age 65. Therefore, although the relation between cigarette smoking and carotid disease remains unestablished, there is some evidence that they may be correlated.…”
Section: -6 7-9 10-12 >12mentioning
confidence: 99%
“…However, 41% of the patients without bruits also had carotid atherosclerosis. Lo et al 14 reported a similar incidence of carotid lesions in asymptomatic patients with bruits. For detecting early carotid atherosclerosis, cervical bruits appear to be an insensitive marker.…”
Section: Resultsmentioning
confidence: 79%
“…Before the introduction of noninvasive imaging methods it was impossible to use a control group that was both asymptomatic and demonstrabry free of atherosclerosis because only patients with symptoms underwent angiography. This situation produced, in general, two kinds of studies: those with symptom-free controls who did not undergo angiography and were therefore not necessarily free of disease 30 " 33 - 37 and those with angiogramnegative controls who were not necessarily symptomfree. 34 - 35 In an effort to assure the symptom-free status of controls in the former studies, many investigators eliminated patients with coronary as well as cerebrovascular symptoms from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, compared with age-and sex-matched controls, Lo et al 37 found plasma concentrations of total cholesterol to be significantly higher in cerebrovascular disease patients with confirmed carotid atheroma.…”
Section: Case-control Studiesmentioning
confidence: 95%